Discrete Geometry for Computer Imagery
DOI: 10.1007/978-3-540-79126-3_4
|View full text |Cite
|
Sign up to set email alerts
|

A First Look into a Formal and Constructive Approach for Discrete Geometry Using Nonstandard Analysis

Abstract: In this paper, we recall the origins of discrete analytical geometry developed by J-P. Reveillès [1] in the nonstandard model of the continuum based on integers proposed by Harthong and Reeb [2,3]. We present some basis on constructive mathematics [4] and its link with programming [5,6]. We show that a suitable version of this new model of the continuum partly fits with the constructive axiomatic of R proposed by Bridges [7]. The aim of this paper is to take a first look at a possible formal and constructive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Using these mappings, it can be shown that the digital curve C d (0, R) is isomorphic to the initial Euclidean circle C(0, R). However, in this article we are concentrating on the properties of the digital curve C d (0, R) (see [13,14] for more details on such a proof).…”
Section: The Arithmetization Methods Applied To Circlesmentioning
confidence: 99%
See 3 more Smart Citations
“…Using these mappings, it can be shown that the digital curve C d (0, R) is isomorphic to the initial Euclidean circle C(0, R). However, in this article we are concentrating on the properties of the digital curve C d (0, R) (see [13,14] for more details on such a proof).…”
Section: The Arithmetization Methods Applied To Circlesmentioning
confidence: 99%
“…The second step consists in computing an upper bound for ||z n − z(t n )|| of equation (13). To do so, we consider ||z n+1 − z(t n+1 )||.…”
Section: Lemma 1 (Arithmetic-geometric Sequence Properties)mentioning
confidence: 99%
See 2 more Smart Citations
“…We consider a new unit which is an infinitely large integer named ω = (ω n ) n∈N , which can be Ω himself. This scaling strongly contracts Z so that the result looks like R [7]. More formally, we defined the Harthong-Reeb with Ω-numbers as follows.…”
Section: The Harthong-reeb Line Based On ω-Numbersmentioning
confidence: 99%